Differential Impacts of the COVID-19 Pandemic on Mental Health Symptoms and Working Conditions for Senior and Junior Doctors in Australian Hospitals. Issue 5 (1st May 2022) - Pascoe, Amy; Johnson, Douglas; Putland, Mark; Willis, Karen; Smallwood, Natasha
Abstract : Australian hospital medical staff experienced extensive disruptions to workplace conditions and suffered a high burden of mental health symptoms during the first year of the COVID-19 pandemic. Exposure to COVID-19 was common despite low caseloads, particularly in junior staff. Despite high levels of resilience, junior staff were especially vulnerable to mental health impacts. Abstract : Objective: This study investigated severity, prevalence, and predictors of workplace disruption and mental health symptoms in Australian junior and senior hospital medical staff during the COVID-19 pandemic. Methods: A cross-sectional survey collected data on demographics, workplace disruption, personal relationships, and mental health. Results: One thousand twenty-one (62.1%) senior and 745 (37.9%) junior medical staff, located primarily in Victoria, completed the survey. Work disruptions were common but varied by seniority, withjunior staff more frequently exposed to COVID- 19 ( P  < 0.001). Symptoms of anxiety, depression, post-traumatic stress disorder and burnout were common but significantly higher in junior doctors ( P   =  0.011 to < 0.001). Common predictors for experiencing mental health symptoms were identified, including prior mental health diagnoses and worsening personal relationships. Conclusions: COVID-19 has had significant but varied impacts on junior and senior doctors, with junior doctors particularly susceptible to harm to mental health. Interventions to safeguard hospital medical staff and prevent attrition of this important workforce are urgently needed.